OPTIMALISASI PENGELOLAAN PENYERTAAN MODAL DAERAH PADA BUMD PERSERODA PERTAMBANGAN DAN PERBANKAN - Endang Sumpena; Achmad Jaka Santos Adiwijaya; Ujang Bahar (Magister Hukum Sekolah Pascasarjana Unida, 2023)
This study aims to determine and analyze the management of Regional Equity Participation (PMD) in Regional Owned Enterprises (PERSERODA) as well as the regulation of supervision of the management of Regional Capital Participation (PMD) in Regional Owned Enterprises (PERSERODA). This research uses a juridical-normative approach that uses a literature study, but as long as it is necessary, interviews (interviews) can be carried out to complete the library research. From the results of the study, it can be seen that the management of PMD in Regional-Owned Enterprises (BUMD) refers to the provisions of the legislation. PMD in managing regional assets through contracts or cooperation with third parties is a regional asset that is not separated and is an unproductive asset or its utilization can still be improved. Meanwhile, the institution authorized to supervise Perseroda engaged in the financial sector is the Financial Services Authority (OJK), while for mining and tourism Perseroda until now there is no external supervisory agency and the supervision carried out is not running as it should, or in other words it has not run optimally.